1983
DOI: 10.1192/bjp.143.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Sadistic Fantasy, Sadistic Behaviour and Offending

Abstract: This paper explores the genesis of sadistic behaviour in men and its relationship to crime. Sixteen male special hospital patients, each with a diagnosis of psychopathic disorder, formed the basis of this descriptive study. In only three cases were the crimes explicable in terms of external circumstances and personality traits. The offences of the remaining 13 cases became comprehensible only when the offender's internal circumstances were explored: investigation revealed repetitive sadistic masturbatory fanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
2
8

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(128 citation statements)
references
References 11 publications
2
114
2
8
Order By: Relevance
“…For example, many researchers propose that the recurrent use of deviant sexual fantasies can lead to the commission of a sexual offence in some offenders, whereby the individual becomes motivated to enact the imagery they have mentally simulated within their fantasies (see MacCulloch, Snowden, Wood, & Mills, 1983;Deu & Edelmann, 1997;Wilson & Jones, 2008). This argument is supported by Maniglio's (2010) recent systematic review involving seven studies and a combined total of 171 sexual murderers, where it was found that deviant sexual fantasies promote sexual murder when combined with early traumatic experiences.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…For example, many researchers propose that the recurrent use of deviant sexual fantasies can lead to the commission of a sexual offence in some offenders, whereby the individual becomes motivated to enact the imagery they have mentally simulated within their fantasies (see MacCulloch, Snowden, Wood, & Mills, 1983;Deu & Edelmann, 1997;Wilson & Jones, 2008). This argument is supported by Maniglio's (2010) recent systematic review involving seven studies and a combined total of 171 sexual murderers, where it was found that deviant sexual fantasies promote sexual murder when combined with early traumatic experiences.…”
Section: Introductionsupporting
confidence: 54%
“…Further, Marshall and Eccles (1991) found, in a sample of 129 child molesters, 22% (n = 28) used child-related fantasies before any sexual involvement with a child. MacCulloch, Snowden, Wood, and Mills (1983) found that 13 out of 16 of their sex offender sample reported spending long periods of time masturbating to sadistic fantasies (including rape, sodomy, kidnap, bondage, flagellation, torture, and killing) before committing their offences. More recently, Dandescu and Wolfe (2003) found that 64.9% of 57 (n = 37) child molesters and 76%…”
Section: Sexual Fantasy and Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Einige deutsche Autoren haben die Befunde zur Fantasietätigkeit bei School Shootern aufgegriffen und in Theorien zur Genese schwerer, zielgerichteter Schulgewalt integriert Hoffmann et al, 2003;Lempp, 2006;Robertz, 2004aRobertz, , 2006b Diese werden als zentraler, auslösender Mechanismus für solche Taten betrachtet (Burgess, Hartman, Ressler, Douglas & McCormack, 1986;Prentky et al, 1989 Umsetzung sadistischer Fantasien steigt zudem, wenn diese wiederholt und ausgelebt werden (MacCulloch et al, 1983;Prentky et al, 1989). Obwohl Intelligenz keinen Einfluss auf die Fantasieinhalte hat, begünstigt sie doch die Qualität ihrer Übersetzung in Verhalten (Prentky et al, 1989;vgl.…”
Section: Fantasieunclassified
“…There has been much work on sadistic fantasies and sadistic sexual offenders (MacCulloch et al, 1983;Maniglio, 2010). However, MacCulloch et al (2000) recognized that no explanation existed for how sadistic fantasies are initiated in the first place.…”
Section: Macculloch Gray and Watt's (2000) Account Of Sadistic Sexumentioning
confidence: 99%